2020
DOI: 10.1002/slct.202001710
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Solution and Solid‐State Fluorescence of 2‐(N‐cycloamino)cinchomeronic Dinitrile Derivatives

Abstract: A facile approach to the synthesis of novel 2‐(N‐cycloamino)cinchomeronic dinitriles showing intense photoluminescence both in solution and solid state was developed. Absorption, fluorescence and solvatochromic properties were investigated. It was found that the 2‐(N‐cycloamino)cinchomeronic dinitrile derivatives containing conjugated aryl moiety show intense emission in nonpolar solvents with fluorescence quantum yield up to 0.8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The mobile halogen atom and two reactive cyano groups will allow a facile modification of the acceptor unit of chromophores by the introduction of the desired moieties. [51][52][53][54][55][56][57][58][59]…”
Section: Introductionmentioning
confidence: 99%
“…The mobile halogen atom and two reactive cyano groups will allow a facile modification of the acceptor unit of chromophores by the introduction of the desired moieties. [51][52][53][54][55][56][57][58][59]…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, there has been an exponential increase in the number of publications about the synthetic approaches to compounds showing dual-state emission (DSE) [ 1 , 2 , 3 , 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. This is due to the fact that DSE molecules are more versatile and are therefore intended for a wider range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that compounds with cinchomeronic dinitrile fragments exhibited fluorescence both in solutions and in solid state [ 39 , 40 , 41 , 42 , 43 ]. For example, sulfur-containing cinchomeronic dinitrile derivatives (ethyl 2-((3,4-dicyanopyridine-2-yl)thio)acetates) showed blue fluorescence in organic solvents and a green emission in powders [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation